Association of ATP-binding cassette sub-family B member 1 gene C3435T polymorphism with neutropenia in breast cancer patients treated with chemotherapy (Faculty of Medicine Universitas Indonesia, 2016)
Background: Neutropenia is the most common adverse event of breast cancer chemotherapy which can be life threatening due to opportunistic infection, neutropenic episodes may lead to delay or reduction of drug doses which may compromise treatment outcomes. In this study, we investigated the association of ATP-binding cassette sub-family B member 1 (ABCB1) gene C3435T polymorphism with the grading of neutropenia in breast cancer patients who treated with doxorubicin-taxan.Methods: 72 Indonesian female breast cancer patients from Haji Adam Malik Hospital who had been diagnosed and treated with doxorubicin-taxane regimen were selected for this cohort study. DNA was extracted from peripheral leucocytes and ABCB1 C3435T polymorphism was analyzed with PCR-RFLP. Patient data were collected from patientâs medical record for 3 cycles of chemotherapy. Association between ABCB1 C3435T polymorphism with neutropenia was assessed using Kruskal-Wallis test. Decline of absolute neutrophil count was assessed using Wilcoxon test. Genotype deviation and allele frequencies were also determined by Hardy-Weinberg Equilibrium.Results: The frequencies of ABCB1 C3435T genotype for wildtype (CC), heterozygous (CT) and homozygous mutant (TT) was 22 (30.6%), 38 (52.8%) and 12 (16.7%) respectively. No association were found between ABCB1 C3435T polymorphism and the grading of neutropenia (p>0.05). There was a difference on the average of absolute neutrophil count after the first chemotherapy and after the third chemotherapy (p<0.05). There was no significant deviation of allele and genotype frequency from Hardy-Weinberg Equilibrium.Conclusion: ABCB1 C3435T polymorphism had no association with the grading of neutropenia in breast cancer patients treated with doxorubicin-taxane regimen, however there was a trend of absolute neutrophil count declining during the 3 cycles of chemotherapy.